2016
DOI: 10.1038/srep35799
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of transgenic soybean seeds by terahertz spectroscopy

Abstract: Discrimination of genetically modified organisms is increasingly demanded by legislation and consumers worldwide. The feasibility of a non-destructive discrimination of glyphosate-resistant and conventional soybean seeds and their hybrid descendants was examined by terahertz time-domain spectroscopy system combined with chemometrics. Principal component analysis (PCA), least squares-support vector machines (LS-SVM) and PCA-back propagation neural network (PCA-BPNN) models with the first and second derivative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 35 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…This result agrees with the work of other researchers [49,50]. However, in some other studies, MSC was not the optimal pretreatment method; rather, these studies reported optimal pretreatment methods of median filter smoothing [51], SG [52] t-distributed stochastic neighborhood embedding (t-SNE) [53], and SNV [54,55]. In the hyperspectral identification of wheat [56] and maize [57] seed varieties, the best models for identifying seed varieties were the 5 point and 3 time smoothing and SNV.…”
Section: Resultssupporting
confidence: 89%
“…This result agrees with the work of other researchers [49,50]. However, in some other studies, MSC was not the optimal pretreatment method; rather, these studies reported optimal pretreatment methods of median filter smoothing [51], SG [52] t-distributed stochastic neighborhood embedding (t-SNE) [53], and SNV [54,55]. In the hyperspectral identification of wheat [56] and maize [57] seed varieties, the best models for identifying seed varieties were the 5 point and 3 time smoothing and SNV.…”
Section: Resultssupporting
confidence: 89%
“…The resulting Tray has a broad application prospect in object imaging, medical [118]  Detection of a carbamate insecticide in food matrices [119]  Moisture content in wheat grain [120] and wafers [121].  Pesticide detection in food powders [122]  Antibiotic detection in food and feed matrices [123]  Discrimination of transgenic crops [130] diagnosis, environmental detection and communication. However, in the frequency range of terahertz radiation, the absorption and group velocity dispersion (GVD) of water vapor controls the propagation of THz waves in the atmosphere [147].…”
Section: B Terahertz Radiationmentioning
confidence: 99%
“…In the past decade, new emerging approach of THz spectroscopy – THz time-domain spectroscopy (TDS) in combination with chemometrics techniques in particular 6 – showed a significant breakthrough in application for food quality inspection 12 . A number of studies has recently reported promising results that are addressed to the discrimination of transgenic crops 13,14 , early wheat grains germination detection 15 , the determination of tea types with the protected geographical indications 16 , as well as the discrimination between edible oils and used frying oils 17 . Recently, Yin et al .…”
Section: Introductionmentioning
confidence: 99%